Single Er3+, Yb3+: KGd3F10 Nanoparticles for Nanothermometry - de Oliveira Lima, Karmel; dos Santos, Luiz Fernando; Galvão, Rodrigo; Tedesco, Antonio Claudio; de Souza Menezes, Leonardo; Gonçalves, Rogéria Rocha (Frontiers in Chemistry, 2021)
Among several optical non-contact thermometry methods, luminescence thermometry is the most versatile approach. Lanthanide-based luminescence nanothermometers may exploit not only downshifting, but also upconversion (UC) mechanisms. UC-based nanothermometers are interesting for biological applications: they efficiently convert near-infrared radiation to visible light, allowing local temperatures to be determined through spectroscopic investigation. Here, we have synthesized highly crystalline Er3+, Yb3+ co-doped upconverting KGd3F10 nanoparticles (NPs) by the EDTA-assisted hydrothermal method. We characterized the structure and morphology of the obtained NPs by transmission electron microscopy, X-ray diffraction, Raman spectroscopy, and dynamic light scattering. Nonlinear spectroscopic studies with the Er3+, Yb3+: KGd3F10 powder showed intense green and red emissions under excitation at 980 and 1550 nm. Two- and three-photon processes were attributed to the UC mechanisms under excitation at 980 and 1550 nm. Strong NIR emission centered at 1530 nm occurred under low 980-nm power densities. Single NPs presented strong green and red emissions under continuous wave excitation at 975.5 nm, so we evaluated their use as primary nanothermometers by employing the Luminescence Intensity Ratio technique. We determined the temperature felt by the dried NPs by integrating the intensity ratio between the thermally coupled 2H11/2→4I15/2 and 4S3/2→4I15/2 levels of Er3+ ions in the colloidal phase and at the single NP level. The best thermal sensitivity of a single Er3+, Yb3+: KGd3F10 NP was 1.17% at the single NP level for the dry state at 300 K, indicating potential application of this material as accurate nanothermometer in the thermal range of biological interest. To the best of our knowledge, this is the first promising thermometry based on single KGd3F10 particles, with potential use as biomarkers in the NIR-II region.